The relationship between neuromyelitis optica spectrum disorder and autoimmune diseases - Lin, Jie; Xue, Binbin; Li, Jia; Xie, Dewei; Weng, Yiyun; Zhang, Xu; Li, Xiang; Xia, Junhui (Frontiers in Immunology, 2024)
Objective Neuromyelitis optica spectrum disorder coexists with connective tissue disorders were reported. The objective of this study is to describe the characteristics of NMOSD coexisting with autoimmune diseases(AID). Methods This retrospective study evaluated NMOSD patients with and without AID. The enrolled patients had at least one attack and the duration was more than 1 year. Data on demographics, clinical features, and laboratory findings were assessed. The Poisson model was used to investigate risk fators associated to the annualized relapse rate, whereas the COX model was used to evaluate the risk factors for the first relapse. Results A total of 180 patients (female:154; male:26) with NMOSD were identified: 45 of whom had AID and 135 of whom did not. Female patients had a higher prevalence of concomitant AID (P=0.006) and a greater relapse rate within the first year. There were no statistically significant differences in characteristics. Kaplan-Meier analysis revealed that NMOSD patients with seropositive AQP4-ab (log-rank: p=0.044), anti-SM (log-rank: p=0.020), and anti-Pmscl (log-rank: p=0.011) had a shorter time to relapse. Patients with seropositive AQP4-ab (HR:2.402, 95%CI:1.092-5.283, p=0.029) and anti-Sm (HR:3.411, 95%CI:1.151-10.102, p=0.027) have a higher risk of suffering their first relapse, according to the COX model. Patients with and without AID showed a similar declining tendency in terms of change in ARR throughout the first five years of the disease. The ARR was greater in the first year (IRR:1.534, 95%CI: 1.111-2.118) and the first 2 years (IRR:1.474, 95%CI: 1.056-2.058) for patients who coexisted with AID diagnosis prior to NMOSD onset. Conclusions NMOSD patients coexisting with AID had a similar characteristics compared with NMOSD patients without AID. NMOSD patients with AID diagnosed before onset had a higher risk of relapse in early stage of disease.